KARISMA K.H. MUHAMMAD ZAINI ABDUL GHANI DAN PERAN SOSIALNYA (1942-2005) - Mirhan, Mirhan (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2013)
In this exposure, the author proposed about KH Muhammad Zaini Abdul Ghani, the study on charisma and social role and Kharisma of KH Muhammad Zaini Abd. Ghani also supported by the ability to master the classical Islamic sciences. He was able to explain the concepts and to construct elaborate religious in simple language. Therefore, when listening to the description of his talk was easy to understand, understood and grown the love (awe) to him. Feelings of love and admiration were also growing in the hearts of thousands of his disciples. Therefore, a lot of people who liked to tell his karamah - Karamah, although teachers themselves said, Karamah not very important for one's piety, but the consistency in doing good, more better than a thousand Karamah. Once passed away into Rahmatullah, the tomb of K.H. Muhammad Zaini Abd. Ghani always visited by the public until now. Hundreds of people come every day from various parts of this city. This shows that his charisma is not lost when the person dies .